WEFE Nexus Leadership Program: IPSR Innovation Profile - Khadka, Manohara; Buchy, Marlene; Koirala, Sanju; Elias, Marlene (CGIAR System Organization, 2024)
The innovation is a transformative leadership program for professionals working in the water, energy, food and environment (WEFE) sectors. Its aim is to create WEFE nexus champions to advance the uptake and implementation of people-centric WEFE approaches, while contributing to greater equality and social inclusion among professionals in these sectors. The program’s specific objectives are: 1. Develop the technical knowledge and analytical, advocacy, and negotiation skills of WEFE sector professionals on WEFE nexus approaches and their operationalization. 2. Develop the transformational leadership capacity of women and men across WEFE sectors to participate meaningfully in nexus discourses, policy processes, decision-making, planning, and implementation. 3. Develop strong and collaborative networks for co-developing and implementing WEFE nexus solutions. 4. Capitalize on women professionals’ assets and develop a cadre of professionals aware of and able to address structural barriers to gender equality and social inclusion within the WEFE sectors. The course is based on adult learning approaches, such as transformation and experiential learning, and including a mentorship element. Participants are professionals (with an emphasis on women) from government, non-governmental organizations (NGOs), civil society organizations (CSOs), natural resources management networks, and the private sector. Developed in Kathmandu, Nepal, the program is designed to be rolled out to the provinces and local levels and other geographies. The innovation was conceptualized and co-developed by GREAT International, Governance Lab, International Water Management Institute (IWMI), and the Alliance of Bioversity and CIAT (ABC)